1998
DOI: 10.1042/cs0950479
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial comparing the effectiveness of two dietary interventions for patients with hyperlipidaemia

Abstract: 1. Intervention trials in free-living populations have shown relatively small reductions in risk factors for cardiovascular disease, including lipid levels, and have led some to question whether diet is an effective treatment for hyperlipidaemia. However, behaviour change is a complex process and it is possible that standard intervention methods fail to motivate people sufficiently to comply with dietary advice.2. This study applied motivational interviewing, a style of behaviour change counselling, to dietary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 15 publications
1
40
0
1
Order By: Relevance
“…Our results indicate that the nurses scored above the mean average (4) in almost all MITI and MISC components. These findings are similar to the skills scores obtained in a trial of MET delivered by trained clinicians in the field of substance abuse [43].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our results indicate that the nurses scored above the mean average (4) in almost all MITI and MISC components. These findings are similar to the skills scores obtained in a trial of MET delivered by trained clinicians in the field of substance abuse [43].…”
Section: Discussionsupporting
confidence: 82%
“…A small number of studies have assessed the delivery of motivational interviewing (MI) based interventions by health professionals such as dieticians [43] specialist cardiac liaison nurses and general nurses [44]. Although interventions have been reported to lead to significant reductions in a number of behavioural and psychological outcomes the use of study specific tools to rate the frequency of MI techniques, as well as a lack of rigorous reporting regarding MI training make it difficult to draw comparisons across studies in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Mhurchu et al [26] randomized 121 adults with hyperlipidemia who were referred to a hospital dietetic service to either standard dietary intervention education or three sessions of AMI. Both groups reported increased dietary knowledge and behavior and significant weight reductions at 3-month follow-up, but no significant change in lipids was found for either group.…”
Section: And Weight Lossmentioning
confidence: 99%
“…The Oslo Study found that regular dietary counseling produced significant long-term declines in serum cholesterol (interpreted as a marker of dietary fat and saturated fat intakes) compared to control participants (46). Motivational interviewing produced no additional changes in dietary fat intake beyond standard nutritional counseling in subjects with hyperlipidemia (68). Women with coronary heart disease reduced calories from fat and saturated fat consumption by half (net reduction of 12% of energy from fat) in a randomized intervention study (110).…”
Section: Individual Randomized Trialsmentioning
confidence: 99%